Birokrasi Dan Politik : Problematika Dalam Keniscayaan Administrasi Publik - Prayitno, Budi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2011)
Local elections in Indonesia have brought immediate changes to the political conditions. Direct Democracy that was expected to bring maturity instead falls apart at the implementation level. Political practice that is driven by money to win particular contestant in turn bring negative effect on bureaucracy that eventually not value-free and filled by political interests. Bureaucracy positions which ought to be neutral nowadays become partitioned off into various attrations of politics. Political party that play vital role as the main gate to construct political maturity of society also experienced failure, although political parties play a vital role to improve governance.